2002
DOI: 10.1007/s00276-001-0399-x
|View full text |Cite
|
Sign up to set email alerts
|

Material properties of trabecular bone structures

Abstract: The transplantation of human allograft for restoration and filling of cortical bone defects is well known. Our aim was an experimental investigation of the mechanical stability of the often used femoral head spongiosa depending on the caliber and extent of the allograft. To evaluate the orientation of the trabecular structures of the femoral head and relate this data to its mechanical properties, morphometric studies were combined with mechanical tests of cancellous bone specimens. The mechanical examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
1
18
1
2
Order By: Relevance
“…The results found in the present study are in disagreement with those reported by Birnbaum et al (2001). This disagreement could be explained by the fact that in their study the specimens were tested along an axis set considering the local anatomy of the proximal femur.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…The results found in the present study are in disagreement with those reported by Birnbaum et al (2001). This disagreement could be explained by the fact that in their study the specimens were tested along an axis set considering the local anatomy of the proximal femur.…”
Section: Discussioncontrasting
confidence: 82%
“…There is only one experimental study (Birnbaum et al, 2001) that can be compared with the present one. The results found in the present study are in disagreement with those reported by Birnbaum et al (2001).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this study, a completely different approach to inferring a force distribution pattern on the human proximal femur has been applied: since the internal trabecular system of bone tissue aligns with the principal stresses, a widely accepted concept [Pauwels, 1954;Rydell, 1973;Osborne et al, 1980;Fyhrie and Carter, 1986;Kerr et al, 1986;Biewener et al, 1996;Cody et al, 1996;Smit et al, 1997;Turner et al, 1997;Uchiyama et al, 1999;Birnbaum et al, 2001;Gomberg et al, 2003;Ruimerman et al, 2003;Kinney et al, 2005], analysis of this internal bone structure may help to clarify the direction of forces acting on bone tissue. In this way, bone itself can serve as a record of its biomechanical history [Carter et al, 1989] and can provide a basis to examine which of the two biomechanical models in question reflects the physiologic situation most appropriately.…”
Section: Introductionmentioning
confidence: 99%